The Effect of Distraction during Labor Induction on Timing of Analgesia Request: A Randomized Clinical Trial - Dixon, C. Luke; Monsivais, Luis; Chamseddine, Petra; Olson, Gayle; Pacheco, Luis D.; Saade, George R.; Costantine, Maged M. (American Journal of Perinatology, 2019)
Objective To assess whether distraction using music and/or video games influences timing of analgesia request and improves pain outcomes in women undergoing labor induction.Study Design A total of 219 pregnant women with singleton gestation undergoing labor induction with a Foley bulb (FB) at term were randomized to distraction with music and video games via iPod (n = 109) or no iPod (n = 110). The primary outcome was the time from FB placement to request for pain medication. Secondary outcomes included number of patients requesting pain medication within 6 and 12 hours, type of pain medication received, pain visual analog scale scores, and patient satisfaction. Mann–Whitney's, chi-square, Kaplan–Meier's curves, and Pearson's product moment correlation were used for statistical analysis (significance: p < 0.05).Results Baseline characteristics were similar between the two groups. There was no difference in the time from FB placement until pain medication request between the groups. There were no significant differences in secondary outcomes. Increased per cent time of iPod use correlated with a longer time until pain medication request (R2 = 0.22, p = 0.03).Conclusion We were not able to show that distraction using music and video games delays timing of analgesia request or improve pain outcomes in pregnant women undergoing mechanical labor induction at term.
Keywords: induction of labor; labor analgesia; music; pain; distraction; pain management